INTER-INDIVIDUAL RESPONSES OF MAXIMAL OXYGEN UPTAKE TO EXERCISE TRAINING: A CRITICAL REVIEW. Issue 22 (1st November 2016) - Williamson, P; Atkinson, G; Batterham, A
Abstract : We recently reported how to quantify the inter-individual differences in response to an intervention. We now aim to scrutinise the research on the individual responses to training of maximal oxygen uptake (VO2 max). The key trigger for further investigation into individual responses is when the standard deviation of change (SDchange ) in the intervention sample is substantially larger than the same standard deviation derived from a suitable comparator sample. 'True' inter-individual response can then be inferred. Six relevant studies from the influential HERITAGE family study were published in the 1980s. Unfortunately, only one of these studies included a comparator arm (1) Re-analysis of data from this study, accounting for random within-subjects variation, revealed an absence of clinically important individual difference in VO2 max response. The SDchange was, in fact, larger (±5.6 ml/kg/min) for the comparator than the intervention group (±3.7 ml/kg/min). Over 180 publications have now resulted from The HERITAGE study, but the crucial comparator arm is absent in all of these studies. Some authors rationalized this absence by claiming that only inter-individual differences in exercise response were of interest. This absence of a comparator sample is also the case in some present on-going studies. Again, re-analysis of data from the most recent studies does not suggest clinically relevant inter-individual differences in response. We also have concerns about the intraclass correlation coefficient approach to data analysis in twin studies. These are often heterogeneous for the obviously influential factors of sex, age and fitness, thereby inflating an unadjusted coefficient. We conclude that most studies on individual differences in VO2 max response have no comparator sample. Therefore, 'true' individual response differences cannot be quantified. For those studies with a comparator sample, the difference between individual differences in response and random within-subjects variation is not clinically relevant.